4x+32=-4x+16x
4x+32=12x
-4x -4x
32=8x
/8 /8
4=x
8x + 9.16 = 4x + 16 8x - 4x = 16 - 9.16 4x = 6.84 x= 1.71
Y- intercept of 4x+8y=16
4x+9=25 4x=16 x=4
48-4x-13=4x+32+x First combine like terms So 48-13-4x=35-4x 4x+x+32=5x+32 Get the x by itself by subtracting the 32 from both sides 35-4x=5x+32 -32 -32 3-4x=5x +4x +4x 3=9x Divide both sides by 9 to get x by itself 3/9=x Simplify 1/3=x
(2, 2)
8x + 9.16 = 4x + 16 8x - 4x = 16 - 9.16 4x = 6.84 x= 1.71
2y = 4x - 16 5y = 4x + 8 Subtract the first equation from the second: 3y = 24 so that y = 8 Substitute this into the first equation: 16 = 4x - 16 ie 32 = 4x so that x = 8 So the solution is (8, 8)
4x+4y=16 y=5 4x+ 20=16 4x=-4 x=-1
Y- intercept of 4x+8y=16
4x+9=25 4x=16 x=4
16
4x - 10 = -4x + 22 +4x+10=+4x +10 8x = 32 x = 4
4x + 3 = 16 Therefore, 4x = 13 x = 13/4 Therefore, x = 3.25
48-4x-13=4x+32+x First combine like terms So 48-13-4x=35-4x 4x+x+32=5x+32 Get the x by itself by subtracting the 32 from both sides 35-4x=5x+32 -32 -32 3-4x=5x +4x +4x 3=9x Divide both sides by 9 to get x by itself 3/9=x Simplify 1/3=x
(2, 2)
x=7 y=4
Presumably this is a simultaneous equation question in the form of: 4x-y = 32 4x+5y = -16 Subtract the bottom equation from the top equation remembering that a -- is equal to a + so 32--16 is +40 and that -+5y-y is -6y: -6y = 48 Divide both sides by -6 to find the value of y: y = -8 Substitute the value of y into the original equations to find the value of x: So: x = 6 and y = -8